Creeping Bentgrass Field Response to Pigment‐Containing Products. (1st July 2014) - McCarty, Lambert B.; Gann, James R.; Wells, Christina E.; Gerard, Patrick D.
Abstract : Reducing summer stress on creeping bentgrass [ Agrostis stolonifera L. var. palustris (Huds.)] putting greens is a major goal of many turf managers. Use of colorants and pigment‐containing products has been proposed as a means of protecting the plant from environmental stress, especially on bentgrass putting greens grown in heat‐stressed environments. The objective of this research was to investigate the physiological effects of four pigment‐containing products–a combination of zinc oxide (ZnO), green pigment, and titanium dioxide (TiO2 ) (TurfScreen); Cu‐based pigments (PAR and Foursome); and a Cu‐pigmented paint designed to provide green color to dormant turfgrass in winter months–have on creeping bentgrass under stressful field conditions. Products were applied weekly for 10 wk to two separate studies repeated in time. TurfScreen, PAR, Foursome, and paint all lowered carbon dioxide exchange rate (CER), reduced normalized difference vegetation index (NDVI), and raised canopy temperature relative to nontreated controls. Only paint lowered visual quality and percent turf cover compared to the untreated controls. TurfScreen reduced evapotranspiration (ET) in one of two studies. Root mass was unaffected by any treatment. Zinc (∼800 mg kg −1 ) and Cu (>155 mg kg −1 ) concentrations in leaf tissue and soil increased dramatically after TurfScreen and paint application, respectively, and potential toxicity should be considered during long‐term use of these products. The products tested failed to enhance physiological processes normally associated with improved turf health and quality.